Dermoid cyst in the floor of the mouth extending to the submental region: A case report and a review - Mujtaba Bala; Ramat Oyebunmi Braimah; Abubakar Abdullahi Bello; Abdurrazaq Olanrewaju Taiwo; Umar Mohammed (Wolters Kluwer Medknow Publications, 2022)
Dermoid cysts in the floor of the mouth or submental region are developmental cysts that occur due to the entrapment of the ectoderm between the second and third branchial arch during embryogenesis around 3rd-5th week of intrauterine life. This report aimed to report the case of a 21-year-old Nigerian woman who presented with a chief complaint of swelling in the floor of the mouth extending to the submental region. There was associated recent history of pain and difficulty in chewing, speaking, and breathing. Clinical, ultrasonography, and histological evaluations were done to establish a diagnosis of an infected dermoid cyst. The infection was treated with antibiotics, after which surgical excision was done under general anesthesia through nasotracheal intubation. The patient was followed up after the surgery and no complication was recorded.